The ethics of sports coaching - Hardman, Alun.; Jones, Carwyn Rhys. (Milton Park, Abingdon, Oxon ; New York : Routledge, 2011)
"Despite the increasing sophistication of our understanding of the player-sport-coach relationship, the dominant perspective of the sports coach is still an instrumental one, focused almost exclusively on performance, achievement and competitive success. In this ground-breaking new book, leading sport scholars challenge that view, arguing that the coaching process is an inherently moral one with an inescapably ethical dimension, involving intense relationships between players and coaches. The Ethics of Sports Coaching critically examines this moral aspect, develops a powerful idea of what sports coaching ought to be, and argues strongly that coaches must be aware of the ethical implications of their acts." -- back cover
The normative aims of coaching: the good coach as an enlightened generalist / Sigmund Loland -- Celebrating trust: virtues and rules in the ethical conduct of sports coaches / Mike McNamee -- Becoming a good coach: coaching and phronesis / t Ethical issues in coaching dangerous sports / Emily Ryall, Steve Olivier -- A defense of expatriate coaching in sport / Cesar R. Torres.
Includes bibliographical references and index.
Keywords: Coaching (Athletics); Sports -- Moral and ethical aspects